Lasting Effects of Intrauterine Exposure to Preeclampsia on Offspring and the Underlying Mechanism - Hui Qing Lu; Rong Hu (Thieme Medical Publishers, Inc., 2019)
Preeclampsia is a common pregnancy complication which can have adverse impact on both mother and baby. In addition to the short term effects, a large body of epidemiological evidence has found preeclampsia can exert long-lasting effects on mother and offspring. Studies suggest that offspring exposed to preeclampsia are at a higher risk of developing cardiovascular, metabolic, and neurological diseases, as well as other diseases. However, studies investigating the underlying mechanism are limited, the exact mechanism still remains unclear. In this study, we will review the epidemiological evidence and studies exploring the mechanism underlying long-term effects of preeclampsia on offspring. Further studies should be targeted at this field so as to implement effective clinical management to prevent the exposed offspring from potential diseases.